Altered Macular Vasculature in Migraine Patients without Aura: Is It Associated with Ocular Vasculature and White Matter Hyperintensities? - Nurdan Gamze Taşlı; Alevtina Ersoy (Journal of Ophthalmology)
Aim. We aimed to determine the alterations in macular and optic nerve vasculature in patients with migraine without aura using optical coherence tomography-angiography (OCTA). We also aimed to determine whether there were clinical differences and alterations in ocular structures in migraine cases with white matter hyperintensities (WMH) using magnetic resonance imaging (MRI). Materials and Methods. The study group comprised patients with migraine without aura and age- and sex-matched healthy controls. Detailed histories of the patients with migraine were recorded including the disease duration, number of attacks in the last month, and attack durations. Visual evoked potentials (VEP) were recorded in all migraine patients. The migraine disability assessment (MIDAS) questionnaire was administered to all patients. The patients were divided into two groups as migraine with WMHs and migraine without WMHs. All subjects underwent a complete neurological and ophthalmological examination. Only the right eyes of the patients were included in the study. Retinal imaging was performed using OCT and OCTA. Results. A total of 66 migraine patients (29 with WMH and 37 without WMH) and 43 healthy controls were included in this study. Among the migraine patients, disease duration, attack frequency in the last month, attack durations, and the visual analogue scale (VAS), MIDAS, and VEP scores were all similar between those with and without WMHs. There was no significant difference between the groups regarding the ganglion cell complex, foveal, and retinal nerve fiber layer thicknesses. The superficial or deep vascular perfusion densities of the optic disc were also similar between the groups. The foveal avascular zone (FAZ) was significantly larger (P=0.034), and both superficial and deep macular vascular densities were significantly lower in the migraine groups compared with the healthy controls (P=0.001). There was no significant difference concerning the FAZ size or vascular densities between the migraine groups with and without WMHs. In the correlation analysis performed between the migraine patients, the FAZ size was correlated with age and VAS and MIDAS scores while both superficial and deep macular vascular densities were negatively correlated with age and VAS and MIDAS scores. Conclusion. We suggest that for not only migraine with aura but also migraine without aura, neurovascular structures play an important role in pathogenesis, and novel studies are warranted to elucidate the alterations in these and determine the significance of WMHs in these patient groups.